Daniel Ratner, "Reducing Food Loss and Waste - Making it Personal" - Ratner, Daniel (2019)
Daniel Ratner SPECIAL EVENT Reducing Food Loss and Waste – Making it Personal Co-Organized by IFPRI, Stop Wasting Food / Selina Juul, World Resources Institute (WRI), Champions 12.3, and the Embassy of Denmark in Washington, DC MAR 12, 2019 - 09:30 AM TO 11:00 AM EDT